Pengaruh Profitabilitas, Leverage, dan Ukuran Perusahaan Terhadap Tax Avoidance (Studi Kasus Pada Perusahaan Sektor Properti dan Real Estate Yang Terdaftar Di BEI): (Studi Kasus pada Perusahaan Sektor Properti dan Real Estate yang Terdaftar di BEI) - Alfina Yanti, Ni Ketut Irna; Wahyuni, Made Arie (Universitas Pendidikan Ganesha, 2025)
This research aims to determine the effect of profitability, leverage, and company size on tax avoidance in property and real estate sector companies listed on IDX. This research uses quantitative methods. The population in this study were property and real estate sector companies listed on the IDX, which are 94 companies. The sample in this study was determined by purposive sampling technique so that 34 companies were obtained that met the criteria. The research period is 2022 - 2024 so that the number of research samples is 102 samples. However, there are 19 outlier data so that the final sample in this study is 83 samples. The data used in this study are secondary data obtained from the company's financial statements. Multiple linear regression analysis was used for the data analysis, including descriptive statistical analysis, classical assumption testing and hypothesis testing, processed using the IBM SPSS application version 27. The results showed that partially profitability and company size have a positive and significant effect on tax avoidance, while leverage has a negative and significant effect on tax avoidance in property and real estate sector companies listed on the IDX in 2022-2024. Simultaneously profitability, leverage, and company size have a significant effect on tax avoidance with an influence level of 21%.